2018
DOI: 10.1021/acs.jafc.8b00904
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and Heavy Metals in the Whole Raw Milk of Dairy Cows from Different Management Systems and Countries of Origin: A Meta-Analytical Study

Abstract: The objective of this meta-analytical study was to investigate selected macrominerals, microminerals, and toxic heavy metals in the bovine whole-raw-milk (WRM) samples of published data. An analytical data set was constructed from 72 different studies from 37 countries with two types of production systems: a conventional production system (CPS) and an organic production system (OPS) compared with commercially available or retail-store-available milk (COM). Results of the meta-analytical study showed difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 69 publications
6
31
1
4
Order By: Relevance
“…Table lists the total calcium content and the contents of different forms of calcium in MLP. The data show that the total calcium content in the MLP reached 16 148.5 mg kg −1 (dry base) – much higher than those of food ingredients as calcium supplement in daily life, such as milk (1200 mg kg −1 ), soy products (3670 mg kg −1 ) and cheese (5900 mg kg −1 ) . The calcium, including water soluble one, calcium pectinate and calcium carbonate, can be absorbed readily, accounting for approximately 60% of the total calcium content.…”
Section: Results and Analysismentioning
confidence: 94%
“…Table lists the total calcium content and the contents of different forms of calcium in MLP. The data show that the total calcium content in the MLP reached 16 148.5 mg kg −1 (dry base) – much higher than those of food ingredients as calcium supplement in daily life, such as milk (1200 mg kg −1 ), soy products (3670 mg kg −1 ) and cheese (5900 mg kg −1 ) . The calcium, including water soluble one, calcium pectinate and calcium carbonate, can be absorbed readily, accounting for approximately 60% of the total calcium content.…”
Section: Results and Analysismentioning
confidence: 94%
“…It should be noted that all the data presented in this study with regards to milk minerals in the 26 dairy farms in Alberta are compared with the data we generated and published in a previous meta-analytical study [6]. The data from this study will also be compared with mineral content of the world raw milk originating from world CONV dairy farms and from world COMM or retail stores.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals such as cadmium (Cd), chromium (Cr), lead (Pb), or nickel (Ni) accumulate in plant materials and consequently pass into the milk and milk products. Recently, we reported that concentrations of two heavy metals including Cd in the raw milk from several areas of India, Nigeria, Palestine, and Slovakia, and Pb from several areas of Brazil, Croatia, Egypt, India, Mexico, Nigeria, Palestine, Serbia, and Turkey were above their MRLs (minimum risk levels) [6]. However, to the best of our knowledge, there is no data published with regards to content of milk metals in the raw milk of dairy cows in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations